Persistence of Crimean-Congo Hemorrhagic Fever Virus RNA - Mathengtheng, Leholonolo; Goedhals, Dominique; Bester, Phillip A.; Goedhals, Jacqueline; Burt, Felicity J. (Emerging infectious diseases, 2020)
Crimean-Congo hemorrhagic fever virus (CCHFV) causes severe disease with fatalities. Awareness of potential sources of infection is important to reduce risk to healthcare workers and contacts. We detected CCHFV RNA in formalin-fixed, paraffin-embedded tissues from a spontaneous abortion that were submitted for histology 9 weeks after a suspected CCHFV infection in the mother.